Effects of Certain Antiepileptics on Behavioral and Electromyographic Seizure Patterns Induced by Maximal Electroshock in Mice - Aya Murakami; Takashi Ishikawa; Kenshi Takechi; Jun Ago; Naotaka Matsumoto; Chiaki Kamei (Elsevier, 2007)
The changes of electromyographic activity (EMG seizure) induced by maximal electroshock were studied in comparison with those of behavioral seizures in mice. In addition, the effects of certain antiepileptics on behavioral seizures and EMG seizure induced by maximal electroshock were also studied. High amplitude with high frequency EMG seizure was observed in parallel with the appearance of tonic extensor (TE) seizure and an intimate relationship was observed between the two parameters. On the other hand, to investigate the intensity of TE seizure, the product of the amplitude and the duration in EMG seizure was calculated, and the effects of antiepileptics on the magnitude of EMG seizure were investigated. As a result, a significant difference was observed at the doses of antiepileptics that showed no significant effects on the durations of TE and EMG seizures; that is, phenytoin, phenobarbital, topiramate, and carbamazepine showed significant effects on the magnitude of EMG seizure at doses of 5, 2, 10, and 5 mg/kg, respectively. From these findings, it may be concluded that this index, that is, the magnitude of EMG seizure induced by maximal electroshock, is a more reliable and highly sensitive method for the assessment of the potential activity of antiepileptics. Keywords:: maximal electroshock, tonic extensor (TE) seizure, clonic (CL) seizure, electromyographic (EMG) activity, EMG seizure